The Analysis Of Character Building Values Found In Aladdin 2019 Movie - Eni Nurhana; Rr. Festi Himatu Karima (Universitas PGRI Adi Buana Surabaya, 2022)
Learning media is a means of communication in conveying information, to facilitate the learning process, and improve the quality of education. movies can be used as learning media. Movies present various kinds of stories that contain values in life such as social values, educational values, and cultural values. One of the movies to choose from is Aladdin 2019 movie. Aladdin 2019 is a movie adaptation from the original animation version 1992. The Aladdin 2019 movie was directed by Guy Richie, written by John August and Guy Richie. The objective of this study is to find out the character building values in the Aladdin 2019 movie and describe the character building values represented in the movie. This study used the formulation of Kemendiknas (2010) and theory from Peterson and Seligman (2004), and perception theory by Mcelmeel (2002). The researchers used descriptive qualitative research. The subject of this study used the subtitle in the Aladdin 2019 movie. The researchers have found 9 character building values in the Aladdin 2019 movie include ,social care, responsible, creative, independent, patriotism, appreciation, communicative/friendly, love of peace, and reading interest. Based on the results of data analysis, it was found that love of peace is the most dominant character building value in the Aladdin 2019 movie.